Koszty docelowe w rachunkowości zarządczej projektów - Klinowski, Marcin (The Organization of Management Accounting in Project Companies, 2009)
Management by projects is more and more often applied by companies nowadays. The foregoing paper presents the chosen components of specificity, company structure location and data processing of management accounting in project companies. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2009, nr 53, s. 38-44